(untitled) (Economic and Political Thought, 2016)
The article analyses the concept of secularization as an element of discourse between knowledge and power, and as social practice constituting a subject in a changing structure of power in the historic process. In this context, the author proposes that, from a broad historical perspective, the Reformation should be understood as a key event in the early modern period when many existing points of reference to subjectivity such as social and religious structures, the essence of time and understanding history were moved. A subject experienced the fall of seemingly indestructible everyday practices and former ways of living. This caused that subjectivity had to go through the process of deconstruction of inadequate self-perception in order to achieve epistemological maturity and reconstruct itself following new rules allowing for practicing ethical existence. This centuries-long process of redefining the subject recognising the changeable areas of the relation between authority and knowledge that was started by the Reformation causes that secularization does not have to be seen as the regression of subjectivity but as “irresistible grace” facilitating the self-recognition of a subject who is better prepared to active presence that is under the pressure of constant change.